Algorithms for survivable routing and wavelength assignment in WDM wavelength-routed mesh networks - Eshoul, AbdElhamid Eswei (University of Ottawa (Canada), 2006)
Due to the huge amount of data that can be lost and the large number of users that can be disrupted during the times of failure in wavelength division multiplexing (WDM) optical networks, reliable optical layer that can quickly and efficiently respond to failures such as fiber cuts is a critical issue to users and service providers. The major challenge in survivable mesh networks is the design of resource allocation algorithms that allocate network resources efficiently while at the same time are able to recover from a failure quickly. This issue is particularly more challenging in optical networks operating under wavelength continuity constraint, where the same wavelength must be assigned on all links in the selected path. This thesis presents a number of schemes to solve the problem of survivable routing and wavelength assignment (RWA) in wavelength-routed WDM networks. The focus is on developing algorithms for survivable RWA in mesh networks that address both resource efficiency and restoration speed under static and dynamic traffic environments. Two different approaches (diverse routing and p-cycles) are pursued to solve the problem of survivable RWA. Their performances and complexities are also compared. Under static traffic, new algorithms have been developed to formulate the RWA as an Integer Linear programming problem using both diverse routing and p-cycles. Under dynamic traffic, new heuristic algorithms are developed to solve the survivable RWA using both approaches and their performances are evaluated and compared using simulations.
Keywords: Engineering, Electronics and Electrical.